Effect of Greater Duckweed Spirodela polyrhiza Supplemented Feed on Growth Performance, Digestive Enzymes, Amino and Fatty Acid Profiles, and Expression of Genes Involved in Fatty Acid Biosynthesis of Juvenile Common Carp Cyprinus carpio - Shrivastav, Avanish Kumar; Kumar, Guddu; Mittal, Prabhat; Tocher, Douglas R.; Glencross, Brett D.; Chakrabarti, Rina; Sharma, JaiGopal (Frontiers in Marine Science, 2022)
The greater duckweed Spirodela polyrhiza (Lemnaceae) is a free floating freshwater macrophyte. The effect of dietary inclusion of duckweed in the feed of common carp Cyprinus carpio fry was evaluated. The control feed (SP0) contained soybean meal as the primary protein source. In four experimental feeds greater duckweed was incorporated at levels of 5 (SP5), 10 (SP10), 15 (SP15) and 20% (SP20) replacing soybean meal. Broken-line regression showed that incorporation of greater duckweed at 10 and 13.4 % levels were breakpoints for final weight and specific growth rate (SGR) of fish, respectively. The final weight and SGR of common carp fed diet SP20 was significantly higher compared to others. Feed conversion ratio was lowest in SP20 treatment. The inclusion of greater duckweed in the fish feeds showed linear relationships with amylase, trypsin, chymotrypsin and lipase activities. The crude protein content was significantly higher in SP10, SP15 and SP20 treatments compared to others. Significantly higher crude lipid and ash contents were found in diet SP20 fed fish compared to others. The essential amino acids composition was similar in five different diets fed fish. The greater duckweed supplemented feeds influenced the fatty acid contents of fish. The monounsaturated fatty acids (MUFA) showed an inverse relationship with the inclusion level of greater duckweed in the feed. Highest MUFA content was found in fish fed SP0 diet. Highest linoleic acid was found in SP20 diet fed fish. The n-3 PUFA contents of fish showed an increasing trend with the increasing inclusion of greater duckweed and significantly higher level was found in SP20 compared to others. Significantly higher expression of fas was found in SP5 and fads2d6 in SP5 and SP10 compared to others. The expressions of elovl2 and elovl5 were significantly higher in SP5, SP10 and SP15 diets fed fish compared to others. The incorporation of greater duckweed in diets improved the growth performance and nutritional value of common carp.